Contemporary Test Performance of the Random Urine Protein-to-creatinine Ratio - Champion, Macie L.; Becker, David A.; McIlwraith, Claire; Blanchard, Christina T.; Szychowski, Jeff M.; Kim, Dhong-Jin; Jauk, Victoria C.; Harper, Lorie M.; Casey, Brian M.; Tita, Alan T. (American Journal of Perinatology, 2022)
Objective The random urine protein-to-creatinine ratio (UPCR) is a screening test used for predicting clinically significant proteinuria (urine protein  ≥ 300 mg) during pregnancy. No consensus exists on the optimal random UPCR cutoff for performing follow-up 24 hour urine (24H) total protein collection. We aim to evaluate the test performance of random UPCR in predicting proteinuria in a contemporary cohort.Study Design This was a retrospective cohort study of pregnant patients at our institution from 2014 to 2018 with a random UPCR and follow-up 24H protein collection. The primary analysis estimated the test characteristics (sensitivity, specificity, positive and negative predictive values) of using random UPCR for the detection of proteinuria defined as urine protein ≥300 mg on 24H protein collection. UPCR cutoffs from 0.10 to 0.30 mg/dL were evaluated, receiver operator characteristic (ROC) curve was constructed, and area under the curve (AUC) was determined. A secondary analysis examined the correlation between UPCR and 24H protein using least squares regression and Pearson correlation.Results Paired UPCR and 24H collection results were available for 1,120 patients. Mean gestational age at time of UPCR was 31.1 ± 5.1 weeks and 687 (61.3%) of patients had a 24H ≥300 mg. UPCR <0.10 mg/dL effectively excluded proteinuria ≥300 mg on 24H collection, while UPCR ≥0.18 mg/dL correctly classifies proteinuria with 91% sensitivity, 57% specificity, 77% positive predictive value, and 79% negative predictive value. UPCR ≥1.07 mg/dL had 100% specificity for 24 hour proteinuria. The area under ROC curve was 0.86. UPCR and 24H collection were highly correlated with a Pearson correlation coefficient of 0.85. After our institution lowered the threshold to obtain a 24H from UPCR ≥0.20 mg/dL to ≥0.10 mg/dL in May 2017, the percentage of patients meeting criteria for 24H collection increased from 57.8 to 84.4%.Conclusion The AUC and Pearson correlation suggest random UPCR is a high performance test for the prediction of proteinuria on 24H. Optimal test performance is dependent upon clinical consideration and upon the implications of the disease or condition. A random UPCR screen positive threshold of 0.18 mg/dL maximizes sensitivity to identify clinically significant proteinuria.Key Points
Keywords: proteinuria; protein-to-creatinine ratio; 24 hour urine